Arquitetura da Base Aérea de Natal na Segunda Guerra Mundial e as mudanças trazidas pelas travessias do Atlântico - Graciete Guerra da Costa (Navigator)
The Parnamirim’s aviation camp existed before World War 2 explosion. When U.S.A joined the big conflict, and the Brazilian Government gave some areas to support the allied troops, Parnamirim took of course a big impulse. The big area was divided in two parts between the asphalted traces of landing, 16-34 and 12-30: On the west side of the traces, the Air Base of Natal was built, and it was known as the “Brazilian Base”. On the east side of the traces it was built the “American Base”, in much larger proportions, it was also called the “Parnamirim Base” or “Parnamirim Field”. When the Government of the United States bagen the construction of the “Parnamirim Field” in november 1940, there were already some buildings there, such as hangars, radio stations, and small installations for different uses. The time for construction extended till march 1944 due to many original plan changes by the north Americans. The American Base had more then 700 buildings, most of them in simple style that became named “barraco”, to support from 400 to 600 airplanes a day, in a demand to Africa. According to the American engineering, the normal duration time of a “barraco” was from 7 to 10 years. But nowadays, even elapsed 42 years from the World War 2, there still exists a considerable number of “barracos”, in full use, though many buildings have been reformed. Besides those, there are still in the Air Base: the small church built during World War 2, the landing traces, the Official’s Casino, the hospital, the cinema, hangars, between others. The construction of this Air Base was helped by ten hangars, installations for inflammables that included twenty tanks of surface made of steel with 528.300 gallons capacity, twelve underground tanks of steel, five platforms and seven fixed water pampers. The installations of the American Air Base permitted to accommodate 1.800 officials and 2.700 sub-officials. The hospital had 178 beds. The buildings had restaurants, banks, radio stations and others, they worked 24 hours a day. When the deactivation of the American Air Base came in October 31 of the year 1945, the Mixed Military Commission Brazil-U.S.A told in a detailed report in September 1946, qualified the buildings and the structures of the “Parnamirim Field” in barely good conditions, even the water tubes and sewers. It is indeed a vast and important historical and architectural inheritance to be studied, registred and preserved.